Developing Reading Test for the First Semester Students of English Education Department at University of HKBP Nommensen Pematangsiantar - Irene Adryani Nababan; Wiwiek Meisuri; Anita Sitanggang (Randwick International of Education and Linguistics Science Journal, 2023)
The significance of reading comprehension in lifelong learning cannot be overstated. It serves as an interactive process that bridges the gap between the reader and the text. Irrespective of the academic level or subject, students must possess strong reading comprehension skills. The assessment and evaluation of students' reading comprehension abilities are integral components of testing. The tests administered to measure students' achievements should strive to provide accurate and reliable information. The purpose of this research is to create a practical, valid, and reliable reading comprehension exam for use in the English Education Department of the Faculty of Teacher Training and Education at the University of HKBP Nommensen Pematangsiantar. This research uses a quantitative method and carries out at the first semester students, academic year 2023/2024. In the development of reading tests, the preferred format utilized is the multiple choice test. There are 25 items. Relatively speaking that the 9,38 score is relatively high. It demonstrates how the exam appears to be able to distinguish between the test subjects. The reliability of this multiple choice reading comprehension test can be inferred from the KR-21 scores, which stand at 58%. The test's evaluation and the field trial's outcome confirm that the test's results are accurate, dependable, and useful in terms of content.